2022
DOI: 10.4103/jfmpc.jfmpc_901_22
|View full text |Cite
|
Sign up to set email alerts
|

Kounis syndrome and atrial fibrillation after bee sting: A case report

Abstract: A BSTRACT Bee sting can lead to allergic reactions which can present as life-threatening emergencies. Kounis syndrome is an acute coronary syndrome caused by mast cell activation after exposure to an allergen. Atrial fibrillation (AF) along with Kounis syndrome after allergen exposure is a rare presentation. A 40-year-old male patient presented to the emergency department (ED) with multiple bee stings to the face and neck. He complained of retrosternal chest pain along with facial pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
0
0
1
Order By: Relevance
“…в своем обзоре 2022г. предлагают тактику лечения пациента с СК II типа [13]. В основе ведения пациента с СК II типа должен быть протокол лечения ОКС с совместным применением ГКС и антигистаминных препаратов.…”
Section: Discussionunclassified
“…в своем обзоре 2022г. предлагают тактику лечения пациента с СК II типа [13]. В основе ведения пациента с СК II типа должен быть протокол лечения ОКС с совместным применением ГКС и антигистаминных препаратов.…”
Section: Discussionunclassified
“…Kadeli et al reported a case of a severe allergic response to the angiography dye, which led to an inferior wall myocardial infarction [7]. Gopinath et al reported a case of bee sting-induced KS with atrial fibrillation [12]. Prasad et al reported a case of multiorgan dysfunction following multiple bee stings [4].…”
Section: Discussionmentioning
confidence: 99%
“…Otro tipo de complicaciones reportadas, no tan comunes, son: trombocitopenia inmunitaria (68) , linfedema (69) , síndrome de Guillain -Barré (70) , neuropatía óptica (71) , infarto pontino y talámico (72) , lesiones renales agudas (73) , síndrome de Wolff-Parkinson-White (74) , síndrome de Kounis (75) , pénfigo foliáceo (76) , por mencionar algunas. Estas complicaciones se deben principalmente a la acción inmunoestimuladora, y a la presencia de múltiples alérgenos proteicos con actividad enzimática e inductores de la IgE presentes en el VAM (18) .…”
Section: Efectos Adversos Del Vamunclassified